The Principles and Practice of Yoga in Cardiovascular Medicine - Basu-Ray, Indranill; Mehta, Darshan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This is the world$1 (Bs first reference book covering the role of Yoga in Cardiovascular Diseases. It details epidemiology, physiology, pathology, prevention, and management of cardiovascular diseases based on the current scientific understanding of Yoga. Seventy-five experts from four continents, including the most notable names, contributed to this work to create the world$1 (Bs first comprehensive reference literature on Yoga in cardiovascular medicine. The chapters cover information related to Yoga, both as prevention and therapy, including coronary artery disease, heart failure, and arrhythmias. In addition, important cardiovascular topics like obesity and diabetes mellitus are also included. A special chapter covers the role of Yoga in the prevention of cardiovascular complications in COVID-19 patients.s
Yoga-A Historical Perspective -- Yoga as Therapy: Ethnomedical Perspective -- Neurophysiology and Neuroanatomy of Meditation -- Effects of Meditation on Psychological, Psychosocial and Physiological Responses to Stress -- Yoga and Autonomic, Vascular and Endothelin Function -- Yoga and Inflammation -- Yoga and Hypertension -- Yoga and Diabetes Mellitus -- Yoga and Obesity -- Yoga and Metabolic Syndrome -- Effects of Yoga on Subclinical Atherosclerosis -- Yoga and Primary Prevention of Cardiovascular Disease -- Yoga and Lifestyle Factors - Diet, Physical activity, Tobacco cessation, Alcohol, and Sleep -- Yoga and Coronary Artery Disease -- Yoga and Heart Failure -- Yoga and Atrial Fibrillation -- Yoga and Implantable Cardioverter: Defibrillator Therapy -- Yoga for Cardiac Surgeries -- Role of Yoga in Cardiovascular Health In HIV Patients. .
Keywords: Internal medicine; Internal Medicine; Cardiovascular Diseases -- therapy; Yoga